GUIDING QUESTIONS TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILLS: RECOUNT TEXT - Muhtar, Siti Nuraeni; Rustina, Lina Rustina; Dalimunthe, R Nadia R P (Jurnal Ilmiah Bina Bahasa, 2020)
This research aimed to find out whether there was an improvement of the students’ skills in writing recount text after using guiding questions as a technique of writing. The method applied in this research was a quantitative method which use one group pre-test and post-test design. Random group sampling is used as the technique in taking a sample. Afterthat, the researcher took one class consist of 31 of second grade students as research participants. This research was held in 6 meetings involved pre-test, four meetings for treatment, and post-test. The instrument of data collecting was a written test. In analyzing the data, the researcher used SPSS v.16 and t-test.